Urban Mobility in Istanbul: Unveiling Gender and Group Dynamics in Pedestrian Walking Speed (International Journal of Built Environment and Sustainability, 2025)
Urban mobility is influenced by a complex interplay between pedestrian behavior, urban design, and social dynamics such as gender and group interactions. This study investigates how these factors shape walking speeds in Istanbul, aiming to inform more efficient and equitable urban design practices. Using advanced video analysis techniques on 1,177 individuals along a major thoroughfare, this research reveals an average walking speed of 1.37 meters per second (m/s). Analysis revealed men (1.41 m/s, N=610) walking faster than women (1.32 m/s, N=567), and groups (1.26 m/s, N=287) slower than solo walkers (1.40 m/s, N=890). These findings underscore the importance of considering diverse user needs and social dynamics in urban planning. By accounting for gender-specific speeds and group behaviors, Istanbul's urban planners can better optimize sidewalk widths, intersection layouts, and social spaces to accommodate a variety of pedestrian experiences. This study contributes to a deeper understanding of pedestrian behavior in a non-Western context, providing valuable insights for creating safer, more accessible, and equitable urban environments in Istanbul.
Keywords: Pedestrian Behavior, Walking Speed, Gender Differences, Group Dynamics, Urban Mobility